Produktivitas Amino Acid Fish Aggregation pada Alat Tangkap Bagan Apung di Perairan Palabuhanratu, Sukabumi - Roza Yusfiandayani; Bambang Riyanto; Mohamad Rafi; . Heriyanto (Jurnal Ilmu Pertanian Indonesia, 2019)
Fish has two chemical sensory/receptor systems that smell (olfactory) and taste (gustatory) odor that adapt to the specific substance of the environment. In general, olfactory is similar to nasal organs for human nostrils. The olfactory receptors detect chemical stimuli in the form of electrical signals. Based on the ability of fish that can respond to chemical stimuli through the sense of smell, a substance can be used to attract the attention of fish. In response to this reality, AFA (Amino Acid Fish Aggregation) can be developed as a fish collecting tool to attract fish bu using amino acid preparation that works though the sense of smell and taste of fish. The objectives of this study were to design and produce a prototype of Amino Acid Fish Aggregation (AFA), to determine the productivity of catches of raft lift net by using AFA, and to calculate the length of the weight of the catch using AFA. The data used were catch data with weights and lengths of fish catch by raft lift net using AFA. The results showed that the AFA prototype which had a size of p x l x t : 35 x 22 x 15 cm and the highest catches was found at 18.00-00.00 WIB by using AFA with raft lift net. The catches using AFA in Palabuhanratu waters amounted to 5 types of fish, namely stolephorus sp., sardinella sp., rastrelliger kanagurta, euthynnus affinis, trichiurus sp., and positive allometrics were found in rastrelliger kanagurta and anchovy, but negative allometrics were found in euthynnus affinis, sardinella sp., and trichiurus sp.